A Qualitative Study on Nutrition and Well-being of Healthcare Shift Workers - Nur Islami Mohd Fahmi Teng; Emmanuel Ngelayang; Norfarhana Md Said; Norsham Juliana Nordin; Nor Amira Syahira Mohd Azmi; Ling-Wei Chen; See Ling Loy (Springer Science and Business Media LLC, 2025)
Indexed by Scopus/ERA